Electronic transport material and preparation method thereof, display device and preparation method thereof

CN115377300BActive Publication Date: 2026-11-03TCL TECHNOLOGY GROUP CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110533104.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-05-17
Publication Date
2026-11-03
Estimated Expiration
2041-05-17

AI Technical Summary

Technical Problem

In existing technologies, electron transport materials such as zinc oxide have a wide particle size distribution and poor film-forming properties, resulting in poor conductivity of the electron transport layer film.

Method used

A capping agent is added during the reaction of metal salt with alkaline solution. The capping agent binds to oxygen vacancies or hydroxyl groups on the surface of metal oxide through N atoms or halogen atoms, coating the surface of nano-metal oxide to form electron transport materials with small and uniform particle size. The capping agent is then removed by vacuum annealing.

Benefits of technology

It improves the film-forming properties and stability of electron transport materials, optimizes the contact interface with adjacent functional layers, and enhances the migration and transport efficiency of charge carriers within the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115377300B_ABST
    Figure CN115377300B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of display, and particularly relates to an electron transport material and a preparation method thereof, and a display device and a preparation method thereof. The preparation method of the electron transport material comprises the following steps: obtaining a metal salt solution and an alkaline solution; mixing the metal salt solution and the alkaline solution, and adding a capping agent in the reaction process of the metal salt and the alkaline substance to continue the reaction, so as to obtain a metal oxide electron transport material with the capping agent combined on the surface; and the capping agent is selected from at least one of an alkane containing an N atom or a halogen atom, a cycloalkane containing an N atom or a halogen atom, and a polymer containing an N atom or a halogen atom. The preparation method of the application can obtain the metal oxide with the capping agent combined on the surface, reduce the aggregation phenomenon of the nanoparticles, ensure the uniformity and dispersion stability of the metal oxide nanoparticles, thereby improving the film-forming property of the electron transport material, the film layer is more compact, and the carrier transport migration efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of display technology, and particularly relates to an electronic transmission material and its preparation method, as well as a display device and its preparation method. Background Technology

[0002] Quantum dots (QDs) are a class of typical nanomaterials with particle sizes within the quantum confinement effect. They not only inherit the characteristics of bulk semiconductors but also exhibit unique optical properties, specifically wide absorption, narrow emission, high yield of fluorescent quantum dots, and good photothermal stability. These unique advantages make them promising for applications in displays, lasers, photovoltaics, and biolabeling. Quantum dot light-emitting diodes (QLEDs), with their unique optical and physical properties such as continuously tunable emission spectra, high brightness, and high color purity, have become strong competitors in the next generation of displays and lighting. QLED devices widely employ a sandwich structure consisting of an anode, an organic hole transport layer, a light-emitting layer, an inorganic electron transport layer, and a metal cathode. QLED display technology based on solution processing has demonstrated significant advantages and potential in the competition for next-generation display applications.

[0003] Currently, the commonly used synthesis method for electron transport layer materials is the sol-gel method. However, the current synthesis process often results in the merging of electron transport material nanoparticles, such as zinc oxide, and a tendency to combine with larger particles. This leads to a wide particle size distribution of the electron transport material, poor film-forming properties of the zinc oxide solution, and consequently, poor conductivity of the electron transport layer film in the device. Summary of the Invention

[0004] The purpose of this application is to provide an electron transport material and its preparation method, as well as a display device and its preparation method, which aims to solve to some extent the problems of wide particle size distribution, poor film formation, and poor conductivity of electron transport thin films caused by existing methods for preparing electron transport materials such as zinc oxide.

[0005] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows:

[0006] In a first aspect, this application provides a method for preparing an electron transport material, comprising the following steps:

[0007] To obtain metal salt solutions and alkaline solutions;

[0008] After mixing the metal salt solution and the alkaline solution, a capping agent is added during the reaction of the metal salt and the alkaline substance to continue the reaction, thereby obtaining a metal oxide electron transport material with a capping agent bound to its surface.

[0009] The capping agent is selected from at least one of the following: alkanes containing N atoms or halogen atoms, cycloalkanes containing N atoms or halogen atoms, and polymers containing N atoms or halogen atoms.

[0010] Secondly, this application provides an electron transport material comprising a metal oxide and a capping agent bonded to the surface of the metal oxide, wherein the capping agent is selected from at least one of: alkanes containing N atoms or halogen atoms, cycloalkanes containing N atoms or halogen atoms, and polymers containing N atoms or halogen atoms.

[0011] Thirdly, this application provides a method for fabricating a display device, comprising the following steps:

[0012] A hole-functional layer and a light-emitting layer are sequentially stacked on a substrate containing an anode;

[0013] After depositing the electron transport material prepared by the above method or the above-mentioned electron transport material on the surface of the light-emitting layer away from the hole functional layer, vacuum annealing is performed to obtain a metal oxide electron transport layer.

[0014] A cathode is fabricated on the surface of the electron transport layer to obtain a display device;

[0015] or,

[0016] After depositing the electron transport material prepared by the above method or the above electron transport material on the cathode surface of the substrate, vacuum annealing is performed to obtain a metal oxide electron transport layer.

[0017] A light-emitting layer, a hole-functional layer, and an anode are sequentially stacked on the surface of the electron transport layer to obtain a display device.

[0018] Fourthly, this application provides a display device, which is prepared by the above-described method for preparing a display device.

[0019] The method for preparing electron transport materials provided in the first aspect of this application involves mixing the metal salt solution and the alkaline solution, and then adding a capping agent during the synthesis of the metal oxide electron transport material to continue the reaction. The capping agent binds to active groups such as oxygen vacancies or hydroxyl groups on the surface of the metal oxide through nitrogen atoms or halogen atoms, thereby coating the surface of the nano-metal oxide and obtaining a metal oxide electron transport material with the capping agent on its surface. The metal oxide nanoparticles coated with the capping agent lose their active sites, reducing the probability of collisions and aggregation between nanoparticles, thus reducing the aggregation phenomenon and ensuring the uniformity and dispersion stability of the metal oxide nanoparticles. This improves the film-forming properties of the electron transport material, resulting in a denser film layer, which is beneficial for improving carrier transport and migration efficiency.

[0020] The electron transport material provided in the second aspect of this application includes a metal oxide and a capping agent such as an alkane, cycloalkanes, or polymer bonded to the surface of the metal oxide by N atoms or halogen atoms. The passivation effect of the capping agent on the surface of the metal oxide nanomaterial not only makes the particle size of the electron transport material more uniform, but also improves the stability of the metal oxide material and reduces the destructive effect of environmental factors on the metal oxide material, thereby improving the carrier migration and transport efficiency of the electron transport material.

[0021] The method for fabricating a display device provided in the third aspect of this application involves depositing the aforementioned electron transport material on the surface of the light-emitting layer or the cathode of a semiconductor device, followed by vacuum annealing to remove the capping agent bonded to the surface of the metal oxide nanomaterial, resulting in a metal oxide electron transport layer. A cathode is then fabricated on the surface of the electron transport layer, or a light-emitting layer, a hole-functional layer, and an anode are fabricated sequentially to obtain the display device. The display device fabricated in this application utilizes the aforementioned electron transport material with small and uniform particle size, resulting in a dense and stable electron transport layer. Furthermore, the contact interface with adjacent functional layers is optimized, improving carrier migration and transport within the device.

[0022] The display device provided in the fourth aspect of this application includes an anode, a hole functional layer, a light-emitting layer, an electron functional layer and an anode that are stacked and bonded together in sequence. The electron functional layer uses the electron transport material with small and uniform particle size mentioned above. Therefore, the electron transport layer has good density and stability, and the contact interface with the adjacent functional layer is optimized, which improves the migration and transport of charge carriers in the device. Attached Figure Description

[0023] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 This is a schematic flowchart of the preparation method of the electronic transport material provided in the embodiments of this application;

[0025] Figure 2 This is a schematic diagram of the positive structure of a quantum dot light-emitting diode provided in an embodiment of this application;

[0026] Figure 3 This is a schematic diagram of the inversion structure of a quantum dot light-emitting diode provided in an embodiment of this application;

[0027] Figure 4This is a schematic diagram of the structure of the electron transport material provided in the embodiments of this application, wherein XR is a capping agent and X is one of N, F, Cl, Br, and I. Detailed Implementation

[0028] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0029] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural.

[0030] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0031] It should be understood that, in the various embodiments of this application, the sequence numbers of the above processes do not imply a sequential order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application. The terminology used in the embodiments of this application is for the purpose of describing specific embodiments only and is not intended to limit this application. The singular forms "a" and "the" used in the embodiments of this application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0032] As attached Figure 1 As shown, the first aspect of this application provides a method for preparing an electron transport material, comprising the following steps:

[0033] S10. Obtain metal salt solution and alkaline solution;

[0034] S20. After mixing the metal salt solution and the alkaline solution, an end-capping agent is added during the reaction of the metal salt and the alkaline substance to continue the reaction, thereby obtaining a metal oxide electron transport material with an end-capping agent bound to its surface.

[0035] The capping agent is selected from at least one of the following: alkanes containing N atoms or halogen atoms, cycloalkanes containing N atoms or halogen atoms, and polymers containing N atoms or halogen atoms.

[0036] The method for preparing electron transport materials provided in the first aspect of this application involves mixing a metal salt solution and an alkaline solution, and then adding a capping agent during the synthesis of the metal oxide electron transport material to continue the reaction. The capping agent binds to active groups such as oxygen vacancies or hydroxyl groups on the surface of the metal oxide through nitrogen atoms or halogen atoms, thereby coating the surface of the nano-metal oxide and obtaining the metal oxide electron transport material with the capping agent on its surface. The metal oxide nanoparticles coated with the capping agent lose their active sites, reducing the probability of collisions and aggregation between nanoparticles, thus reducing the aggregation phenomenon and ensuring the uniformity and dispersion stability of the metal oxide nanoparticles. This improves the film-forming properties of the electron transport material, resulting in a denser film layer, which is beneficial for improving carrier transport and migration efficiency.

[0037] In some embodiments, in step S10 above, the metal salt in the metal salt solution is selected from at least one of zinc salt, titanium salt, tin salt, zirconium salt, and indium salt. In some specific embodiments, the zinc salt includes at least one of zinc acetate and zinc chloride. In some specific embodiments, the titanium salt includes at least one of titanium acetate and titanium chloride. In some specific embodiments, the tin salt includes at least one of tin acetate and tin chloride. The metal salts used in the above embodiments of this application all have good solubility in organic solvents and can all react with alkaline substances to produce metal oxide nanomaterials in situ.

[0038] In some embodiments, the metal salt is selected from at least one of zinc salt, titanium salt, tin salt, zirconium salt, and indium salt, and the metal salt further includes at least one of magnesium salt, aluminum salt, calcium salt, and lithium salt. This application embodiment, by adding magnesium salt, aluminum salt, calcium salt, lithium salt, etc., to the reaction system, thereby doping the metal oxide with metal elements such as magnesium, aluminum, calcium, and lithium, can further improve the electron transport performance of the metal oxide nanomaterial.

[0039] In some embodiments, the solvent in the metal salt solution is selected from at least one of dimethyl sulfoxide, N,N-dimethylformamide, and tetrahydrofuran. These organic solvents have good solubility for the metal salts of this application, providing a suitable solvent system for the reaction between the metal salt and the alkaline substance.

[0040] In some embodiments, the alkaline substance in the alkaline solution is selected from at least one of tetramethylammonium hydroxide, lithium hydroxide, potassium hydroxide, and sodium hydroxide; these alkaline substances can all react with metal salts to generate metal oxide nano-semiconductor materials.

[0041] In some embodiments, the solvent in the alkaline solution is selected from at least one of ethanol, methanol, propanol, isopropanol, and butanol, all of which have good dissolving properties for alkaline substances.

[0042] In some embodiments, in step S20 above, after the metal salt reacts with the alkaline substance for 0.5 to 5 hours, the metal oxide nanoparticles such as ZnO, TiO2, SnO, ZrO2, In2O3, ZnMgO, and AlZnO generated during this reaction time period have relatively small particle sizes. In this reaction stage, a capping agent is added to continue the reaction for 15 to 20 hours. The capping agent binds to the surface of the metal oxide nanoparticles, inhibiting the continued nucleation and growth of the metal oxides and reducing the aggregation phenomenon between nanoparticles. This ensures the uniformity and dispersion stability of the metal oxide nanoparticles, thereby improving the film-forming properties of the electron transport material, making the film layer more compact, and which is beneficial to improving the carrier transport and migration efficiency. In some specific embodiments, the capping agent is added after the metal salt solution and alkaline solution have reacted for 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, or 5 hours. The earlier the capping agent is added, the smaller and more uniform the particle size of the prepared metal oxide will be. If the capping agent is added too early, it will reduce the efficiency of the reaction between the metal salt and the alkaline substance to form metal oxides. If the capping agent is added too late, the generated metal oxide particles will be too large, which is not conducive to the control of the nanoparticle size.

[0043] The capping agents used in this application are selected from at least one of the following: alkanes containing N atoms or halogen atoms, cycloalkanes containing N atoms or halogen atoms, and polymers containing N atoms or halogen atoms. On one hand, these capping agents, containing N atoms and halogen atoms, can bind to oxygen vacancies on the surface of metal oxides generated in the solution system. Alternatively, because the surface of the metal oxide prepared by sol-gel has a large number of hydroxyl groups, the capping agent can form hydrogen bonds with the hydroxyl groups on the surface of the metal oxide, thereby binding to the surface of the metal oxide nanoparticles and forming a metal oxide electron transport material with the capping agent bound to its surface. On the other hand, after the electron transport material in this application embodiment is deposited into a film, these capping agents can be removed from the film layer by vacuum annealing, avoiding the influence of the capping agents on the carrier migration and transport performance.

[0044] In some embodiments, the alkane containing nitrogen or halogen atoms in the capping agent has 2 to 16 carbon atoms; the cycloalkanes containing nitrogen or halogen atoms have 3 to 16 carbon atoms. In some embodiments, the alkane contains branches. In the embodiments of this application, the alkane capping agent preferably has 2-16 carbon atoms, and the cycloalkanes preferably have 3-16 carbon atoms. Under these conditions, the capping agent can effectively prevent further growth and aggregation of the metal oxide, thereby obtaining metal oxides with small and uniform particle size. If the carbon chain of the capping agent is too long, the viscosity of the capping agent will be too high, or it may not be able to fully dissolve in the reaction system. Furthermore, it is also not conducive to the removal of the capping agent by vacuum annealing during subsequent device fabrication.

[0045] In some embodiments, polymers containing N atoms or halogen atoms can be well dissolved in the reaction system and have a low boiling point, not exceeding 300°C, which is beneficial for removal by vacuum annealing during subsequent device fabrication.

[0046] In some specific embodiments, the capping agent is selected from at least one of diethylamine, chlorobenzene, bromobenzene, and polyvinylpyrrolidone. These capping agents have good solubility, good bonding performance with metal oxide surfaces, and are easily removed by vacuum annealing.

[0047] In some embodiments, after mixing the metal salt solution and the alkaline solution, the molar ratio of the metal salt to the alkaline substance in the mixed solution is 1:(1.2~1.8). Under this molar ratio, the metal salt and the alkaline substance can react well to form metal oxides. If the proportion of alkaline substance is too high, the excess alkaline substance will combine with the metal element to form alkali metal precipitates, reducing the generation efficiency of metal oxide nanomaterials, resulting in low purity, and also affecting the subsequent encapsulation effect of the end-capping agent on the metal oxide nanomaterials. In some specific embodiments, after mixing the metal salt solution and the alkaline solution, the molar ratio of the metal salt to the alkaline substance in the mixed solution can be 1:1.2, 1:1.5, 1:1.6, and 1:1.8, etc.

[0048] In some embodiments, the step of mixing the metal salt solution and the alkaline solution includes: adding the alkaline solution dropwise to the metal salt solution at a temperature of 40°C to 60°C for mixing, so that the added alkaline substance reacts with the metal salt to form a metal oxide. If too much alkaline substance is added at once or the addition rate is too fast, the excessive amount of alkaline substance added at once will not have enough time to react with the metal salt to form a metal oxide, and will easily combine with the metal element to form an alkali metal precipitate.

[0049] The method for preparing the electronic transmission material in this application can be used to prepare the electronic transmission materials in the following embodiments.

[0050] As attached Figure 4As shown, a second aspect of this application provides an electronic transport material comprising a metal oxide and a capping agent bonded to the surface of the metal oxide, wherein the capping agent is selected from at least one of: alkanes containing N atoms or halogen atoms, cycloalkanes containing N atoms or halogen atoms, and polymers containing N atoms or halogen atoms.

[0051] The electron transport material provided in the second aspect of this application includes metal oxides and end-capping agents such as alkanes, cycloalkanes, and polymers that are bonded to the surface of the metal oxides through N atoms or halogen atoms. The passivation effect of the end-capping agents on the surface of the metal oxide nanomaterials not only makes the particle size of the electron transport material more uniform, but also improves the stability of the metal oxide material and reduces the destructive effect of environmental factors on the metal oxide material, thereby improving the carrier migration and transport efficiency of the electron transport material.

[0052] In some embodiments, the particle size of the electron transport material is 1–25 μm. The small and uniform particle size can improve the film density and uniformity of the electron transport layer, thereby improving the stability of the film.

[0053] In some embodiments, the metal oxide includes at least one of ZnO, TiO2, SnO, ZrO2, In2O3, ZnMgO, and AlZnO, all of which are metal oxide electron transport materials with high electron migration efficiency.

[0054] In some embodiments, the capping agent is selected from at least one of diethylamine, chlorobenzene, bromobenzene, and polyvinylpyrrolidone.

[0055] A third aspect of this application provides a method for fabricating a display device, comprising the following steps:

[0056] S30. A hole functional layer and a light-emitting layer are sequentially stacked on a substrate containing an anode;

[0057] S40. After depositing the above-mentioned electron transport material on the surface of the light-emitting layer away from the hole functional layer, vacuum annealing is performed to obtain a metal oxide electron transport layer.

[0058] S50. A cathode is fabricated on the surface of the electron transport layer to obtain a display device;

[0059] or,

[0060] S60. After depositing the above-mentioned electron transport material on the cathode surface of the substrate, vacuum annealing is performed to obtain a metal oxide electron transport layer;

[0061] S70. A light-emitting layer, a hole-functional layer, and an anode are sequentially stacked on the surface of the electron transport layer to obtain a display device.

[0062] The method for fabricating a display device provided in the third aspect of this application involves depositing the aforementioned electron transport material on the surface of the light-emitting layer or the cathode of a semiconductor device, followed by vacuum annealing to remove the capping agent bound to the surface of the metal oxide nanomaterial, resulting in a metal oxide electron transport layer. A cathode is then fabricated on the surface of the electron transport layer, or a light-emitting layer, a hole-functional layer, and an anode are fabricated sequentially to obtain the display device. The display device fabricated in the embodiments of this application, due to the use of the aforementioned electron transport material with small and uniform particle size, exhibits good density and stability in its electron transport layer, and optimizes the contact interface with adjacent functional layers, thereby improving the migration and transport of charge carriers within the device.

[0063] In some embodiments, the step of preparing the electron transport layer includes: depositing a solution of the electron transport material of a certain concentration onto the surface of the light-emitting layer or the cathode through processes such as drop coating, spin coating, immersion, coating, printing, and vapor deposition; controlling the thickness of the electron transport layer, approximately 20 to 60 nm, by adjusting the concentration of the solution, the deposition rate (preferably, the rotation speed is between 3000 and 5000 rpm), and the deposition time; and then annealing the solution for 0.5 to 2 hours at a temperature of 70°C to 90°C and a vacuum degree not exceeding 0.0001 Pa to form a film, thereby fully removing the solvent and the surface-bound capping agent.

[0064] In some embodiments, the metal oxide includes at least one of ZnO, TiO2, SnO, ZrO2, In2O3, ZnMgO, and AlZnO, with a particle size of 1–25 μm.

[0065] In some embodiments, in order to obtain high-quality light-emitting devices, the substrate often needs to undergo a pretreatment process. The pretreatment steps include: cleaning the substrate, such as ITO conductive glass, with a cleaning agent to initially remove the stains on the surface, then ultrasonically cleaning it for 20 minutes in deionized water, acetone, anhydrous ethanol, and deionized water respectively to remove impurities on the surface, and finally drying it with high-purity nitrogen to obtain the ITO positive electrode.

[0066] In some embodiments, the choice of substrate is not limited; a rigid substrate or a flexible substrate can be used. In some specific embodiments, the rigid substrate includes, but is not limited to, one or more of glass and metal foil. In some specific embodiments, the flexible substrate includes, but is not limited to, one or more of polyethylene terephthalate (PET), polyethylene terephthalate (PEN), polyetheretherketone (PEEK), polystyrene (PS), polyethersulfone (PES), polycarbonate (PC), polyarylate (PAT), polyarylate (PAR), polyimide (PI), polyvinyl chloride (PV), polyethylene (PE), polyvinylpyrrolidone (PVP), and textile fibers.

[0067] In some embodiments, the selection of the anode material in the above steps is not limited and can be selected from doped metal oxides, including but not limited to one or more of indium-doped tin oxide (ITO), fluorine-doped tin oxide (FTO), antimony-doped tin oxide (ATO), aluminum-doped zinc oxide (AZO), gallium-doped zinc oxide (GZO), indium-doped zinc oxide (IZO), magnesium-doped zinc oxide (MZO), and aluminum-doped magnesium oxide (AMO). It can also be selected from composite electrodes consisting of doped or undoped transparent metal oxides sandwiching metal, including but not limited to one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2, and TiO2 / Al / TiO2.

[0068] In some embodiments, the step of preparing the hole functional layer in the above steps includes: depositing a prepared solution of hole injection or hole transport material into a film on the surface of a substrate such as ITO or a light-emitting layer through processes such as drop coating, spin coating, immersion, coating, printing, and vapor deposition; controlling the film thickness by adjusting the concentration of the solution, the deposition rate, and the deposition time; and then performing thermal annealing treatment at an appropriate temperature.

[0069] In some embodiments, the hole functional layer includes a hole transport layer and a hole injection layer.

[0070] In some embodiments, the hole injection layer includes, but is not limited to, one or more of organic hole injection materials, doped or undoped transition metal oxides, and doped or undoped metal chalcogenides. In some specific embodiments, the organic hole injection materials include, but are not limited to, one or more of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS), copper phthalocyanine (CuPc), 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane (F4-TCNQ), and 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazabenzophenanthrene (HATCN). In some specific embodiments, the transition metal oxides include, but are not limited to, one or more of MoO3, VO2, WO3, CrO3, and CuO. In some specific embodiments, the metal chalcogenides include, but are not limited to, one or more of MoS2, MoSe2, WS2, WSe2, and CuS.

[0071] In some embodiments, the hole transport layer may be selected from organic materials and / or inorganic materials with hole transport capabilities. In some specific embodiments, organic materials with hole transport capabilities include, but are not limited to, poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) (TFB), polyvinylcarbazole (PVK), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine) (poly-TPD), poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine) (PFB), 4,4,4”-tris(carbazole-9-yl)triphenylamine (TCTA), 4,4'-bis(9-carbazole)biphenyl (CBP), N... One or more of N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD) and N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB). In some specific embodiments, the inorganic materials with hole transport capability include, but are not limited to, one or more of doped graphene, undoped graphene, C60, doped or undoped MoO3, VO2, WO3, CrO3, CuO, MoS2, MoSe2, WS2, WSe2, and CuS.

[0072] In some embodiments, the step of preparing the light-emitting layer in the above steps includes: depositing a light-emitting material solution of a certain concentration onto the surface of the hole transport layer or the electron transport layer through processes such as drop coating, spin coating, immersion, coating, printing, and vapor deposition; controlling the thickness of the light-emitting layer, approximately 20 to 60 nm, by adjusting the concentration of the solution, the deposition rate, and the deposition time; and drying at an appropriate temperature.

[0073] In some embodiments, the light-emitting layer includes quantum dot materials, including but not limited to: at least one semiconductor compound from Groups II-IV, II-VI, II-V, III-V, III-VI, IV-VI, I-III-VI, II-IV-VI, and II-IV-V of the periodic table, or a core-shell structure semiconductor compound composed of at least two of the aforementioned semiconductor compounds. In some specific embodiments, the quantum dot functional layer material is selected from: at least one semiconductor nanocrystalline compound from CdSe, CdS, CdTe, ZnO, ZnSe, ZnS, ZnTe, HgS, HgSe, HgTe, and CdZnSe, or a semiconductor nanocrystalline compound with a mixed type, gradient mixed type, core-shell structure type, or combined type structure composed of at least two of the aforementioned semiconductor nanocrystalline compounds. In other specific embodiments, the quantum dot functional layer material is selected from at least one semiconductor nanocrystalline compound selected from InAs, InP, InN, GaN, InSb, InAsP, InGaAs, GaAs, GaP, GaSb, AlP, AlN, AlAs, AlSb, CdSeTe, and ZnCdSe, or a semiconductor nanocrystalline compound with a mixed type, gradient mixed type, core-shell structure type, or combined type of at least two components. In other embodiments, the quantum dot functional layer material is selected from at least one of perovskite nanoparticle materials (especially luminescent perovskite nanoparticle materials), metal nanoparticle materials, and metal oxide nanoparticle materials. All of the above quantum dot materials possess the characteristics of quantum dots and exhibit good photoelectric properties.

[0074] In some embodiments, the particle size of the quantum dot material ranges from 2 to 10 nm. If the particle size is too small, the film-forming properties of the quantum dot material deteriorate, and the energy resonance transfer effect between quantum dot particles becomes significant, which is not conducive to the application of the material. If the particle size is too large, the quantum effect of the quantum dot material weakens, resulting in a decrease in the photoelectric performance of the material.

[0075] In a further embodiment, the obtained display device is packaged. This packaging process can be performed using conventional machine packaging or manual packaging. Preferably, the oxygen and water content in the packaging environment is both below 0.1 ppm to ensure the stability of the device.

[0076] In some specific embodiments, as shown in the appendix Figure 2 As shown, the display device has a positive structure, including an anode disposed on a substrate, a hole functional layer such as a hole injection layer and a hole transport layer deposited on the surface of the anode, a light-emitting layer deposited on the surface of the hole functional layer, an electronic functional layer such as an electron transport layer deposited on the surface of the light-emitting layer, and a cathode deposited on the surface of the electronic functional layer.

[0077] In other specific embodiments, as shown in the appendix Figure 3As shown, the display device has an inverted structure, including a substrate, a cathode deposited on the surface of the substrate, an electron transport layer and other electronic functional layers deposited on the surface of the cathode, a light-emitting layer deposited on the surface of the electron functional layers, a hole transport layer, a hole injection layer and other hole functional layers deposited on the surface of the light-emitting layer, and an anode deposited on the surface of the hole functional layers.

[0078] The fourth aspect of this application provides a display device, which is prepared by the above-described method for preparing a display device.

[0079] The display device provided in the fourth aspect of the present application includes an anode, a hole functional layer, a light-emitting layer, an electron functional layer and an anode that are stacked and bonded together in sequence. The electron functional layer uses the electron transport material with small and uniform particle size mentioned above. Therefore, the electron transport layer has good density and stability, and the contact interface with the adjacent functional layer is optimized, which improves the migration and transport of charge carriers in the device.

[0080] To enable those skilled in the art to clearly understand the above-described implementation details and operations of this application, and to demonstrate the significant advancements in the electronic transmission materials and their preparation methods, as well as the preparation methods of display devices in the embodiments of this application, the following examples illustrate the above technical solutions.

[0081] Example 1

[0082] An electron transport material, the preparation of which includes the following steps:

[0083] ① Weigh 3 mmol of zinc acetate dihydrate and place it in a three-necked flask. Add 30 ml of ultra-dry solvent DMSO to dissolve and obtain a metal salt solution.

[0084] ② Weigh 5 mmol of tetramethylammonium hydroxide (TMAH) into a plastic beaker, add 10 ml of ultra-dry ethanol, and dissolve to obtain an alkaline solution;

[0085] ③ Place the zinc acetate solution in a 50℃ water bath, stir, and wait until the temperature is constant. Then, use a constant pressure dropper to add the TMAH solution dropwise into the zinc acetate solution.

[0086] ④ After stirring and reacting for 0.5 hours, 1 hour, 2 hours, and 5 hours respectively, diethylamine was added, with the molar ratio of zinc to diethylamine being 1:5, 1:20, and 1:50 respectively, and the reaction was continued for 20 hours; as shown in Table 1.

[0087] ⑤ Stop stirring, pour the solution into a centrifuge tube, add excess ethyl acetate to obtain a turbid solution, centrifuge at 3000 rpm, discard the supernatant, add an appropriate amount of ultra-dry ethanol to redissolve the precipitate, and obtain zinc oxide ethanol solution.

[0088] A display device, the fabrication of which includes the following steps:

[0089] ⑥ On an ITO substrate, spin-coat PEDOT:PSS at 5000 rpm for 30 seconds, then heat at 150°C for 15 minutes to form a hole injection layer with a thickness of 20 nm.

[0090] ⑦ Spin-coat TFB (8 mg / mL) at 3000 rpm for 30 seconds, then heat at 150°C for 30 minutes to form a hole transport layer with a thickness of 30 nm.

[0091] ⑧ Spin-coat quantum dots (20 mg / mL) at 2000 rpm for 30 seconds to form a quantum dot luminescent layer with a thickness of 30 nm;

[0092] ⑨ Spin-coating of zinc oxide ethanol solution (30 mg / mL) from Example 1 at 3000 rpm for 30 seconds, followed by treatment at 80°C and 0.001 Pa for 2 hours in a vacuum annealing station to a thickness of 40 nm, forming an electron transport layer;

[0093] ⑩ Electrodes are deposited on the ETL layer and then packaged to obtain the display device.

[0094] Example 2

[0095] An electron transport material is prepared in a manner that differs from that in Example 1 in that chlorobenzene is added as a capping agent in step ④, and the specific addition time and molar ratio are shown in Table 2.

[0096] A display device, the preparation of which differs from that of Example 1, wherein the electron transport material prepared in Example 2 is used in step 9.

[0097] Example 3

[0098] An electron transport material is prepared in a manner that differs from that in Example 1 in that: in step ④, bromobenzene is added as a capping agent, and the specific addition time and molar ratio are shown in Table 3.

[0099] A display device, the preparation of which differs from that of Example 1, wherein the electron transport material prepared in Example 3 is used in step 9.

[0100] Example 4

[0101] An electron transport material is prepared in a manner that differs from that in Example 1 in that: in step ④, PVP (polyvinylpyrrolidone) is added as a capping agent, and the specific addition time and molar ratio are shown in Table 3.

[0102] A display device, the preparation of which differs from that of Example 1, wherein the electron transport material prepared in Example 4 is used in step 9.

[0103] Comparative Example 1

[0104] An electron transport material is prepared in a manner that differs from that in Example 1 in that the capping agent in step ④ is added after stirring for 10 hours and 15 hours, respectively, as shown in Table 1.

[0105] A display device, the preparation of which differs from that of Example 1, wherein the electron transport material prepared in Comparative Example 1 is used in step 9.

[0106] Comparative Example 2

[0107] An electron transport material is prepared in a manner that differs from that in Example 2 in that the capping agent in step ④ is added after stirring for 10 hours and 15 hours, respectively, as shown in Table 2.

[0108] A display device, the preparation of which differs from that of Example 1, wherein the electron transport material prepared in Comparative Example 2 is used in step 9.

[0109] Comparative Example 3

[0110] An electron transport material is prepared in a manner that differs from that in Example 3 in that the capping agent in step ④ is added after stirring for 10 hours and 15 hours, respectively, as shown in Table 3.

[0111] A display device, the preparation of which differs from that of Example 1, uses the electron transport material prepared in Comparative Example 3 in step 9.

[0112] Comparative Example 4

[0113] An electron transport material is prepared in a manner that differs from that in Example 4 in that the capping agent in step ④ is added after stirring for 10 hours and 15 hours, respectively, as shown in Table 4.

[0114] A display device, the preparation of which differs from that of Example 1, wherein the electron transport material prepared in step 9 is used in Comparative Example 4.

[0115] Comparative Example 5

[0116] An electron transport material, the preparation steps of which differ from those of Example 1 are as follows: in step ④, no capping agent is added, and step ⑤ is carried out after reacting directly for 0.5 hours, 1 hour, 2 hours, 5 hours, 10 hours, 15 hours, and 20 hours.

[0117] A display device, the preparation of which differs from that of Example 1, wherein the electron transport material prepared in step 9 is used in Comparative Example 5.

[0118] Furthermore, in order to verify the progressiveness of the embodiments of this application, the particle size of the metal oxide particles in the electron transport layer of the display devices prepared in Examples 1-4 and Comparative Examples 1-4 was measured, and the test results are shown in Tables 1-4 below.

[0119] Table 1

[0120]

[0121]

[0122] Table 2

[0123]

[0124] Table 3

[0125]

[0126]

[0127] Table 4

[0128]

[0129] As can be seen from the test results in Tables 1-4 above, the electron transport materials prepared by adding capping agents in Examples 1-4 and Comparative Examples 1-4 of this application have small particle sizes and narrow particle size distributions. Comparative Example 5, which did not add capping agents, has a wide particle size distribution, poor uniformity, and larger particle size.

[0130] Furthermore, this application tested the external quantum efficiency (EQE) and lifetime T95@1000nit of some display devices in Examples 1-4 and Comparative Examples 1-5, and the test results are shown in the table below:

[0131] Table 5

[0132]

[0133]

[0134]

[0135] As shown in Table 5 above, the external quantum efficiency and device lifetime of the display devices prepared by the electron transport materials in Examples 1-4 were not affected by the addition of the capping agent. On the contrary, the improved photoelectric performance of the devices was enhanced to some extent due to the increased density of the electron transport film. However, in Comparative Examples 1-4, where the capping agent was added in the later stages of synthesis (10 hours and 15 hours), the particles had already undergone a ripening and growth process in the later stages of synthesis, with a particle size of about 20-30 nm. The larger particle size of the electron transport film layer led to an increase in the conductivity of the electron transport layer, resulting in a severe excess of electrons in the device, thereby reducing the device efficiency and device lifetime. In Comparative Example 5, since no capping agent was added at any of the synthesis times, the electron transport material had a wider particle size distribution after film formation, and the particle size was larger than that of the electron transport materials in Examples 1-4 where the capping agent was added during the synthesis process. This is because particles without end-capping agents have high surface energy, causing them to aggregate during storage and film formation. This leads to particle growth, uneven particle distribution, and the presence of large-diameter particles, which affects the film quality, reduces the optoelectronic performance of the device, and may even cause short circuits, resulting in severe leakage and deterioration of device performance.

[0136] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A method for preparing an electron transport material, characterized in that, Includes the following steps: To obtain metal salt solutions and alkaline solutions; After mixing the metal salt solution and the alkaline solution, and after the metal salt reacts with the alkaline substance for 0.5 to 5 hours, a capping agent is added and the reaction continues for 15 to 20 hours to obtain a metal oxide electron transport material with a capping agent on its surface. The capping agent is bound to oxygen vacancies or hydroxyl groups on the surface of the metal oxide through halogen atoms. The capping agent is selected from at least one of chlorobenzene and bromobenzene.

2. The method for preparing the electron transport material as described in claim 1, characterized in that, The molar ratio of the metal element in the metal salt to the capping agent is 1:(5~50).

3. The method for preparing the electron transport material as described in claim 2, characterized in that, The metal salt is selected from at least one of the following: zinc salt, titanium salt, tin salt, zirconium salt, and indium salt; And / or, the solvent in the metal salt solution is selected from at least one of: dimethyl sulfoxide, N,N-dimethylformamide, and tetrahydrofuran; And / or, the alkaline substance is selected from at least one of tetramethylammonium hydroxide, lithium hydroxide, potassium hydroxide, and sodium hydroxide; And / or, the solvent in the alkaline solution is selected from at least one of ethanol, methanol, propanol, isopropanol, and butanol.

4. The method for preparing the electron transport material as described in claim 3, characterized in that, The step of mixing the metal salt solution and the alkaline solution includes: adding the alkaline solution dropwise to the metal salt solution at a temperature of 40°C to 60°C for mixing; And / or, after mixing the metal salt solution and the alkaline solution, the molar ratio of the metal salt to the alkaline substance in the mixed solution is 1:(1.2~1.8). And / or, the metal salt further includes at least one of magnesium salt, aluminum salt, calcium salt, and lithium salt.

5. An electron transport material prepared by the preparation method according to any one of claims 1-4, characterized in that, The electron transport material comprises a metal oxide and a capping agent bonded to the surface of the metal oxide, wherein the capping agent is selected from at least one of chlorobenzene and bromobenzene, and wherein the capping agent is bonded to oxygen vacancies or hydroxyl groups on the surface of the metal oxide via halogen atoms.

6. The electron transport material as described in claim 5, characterized in that, The particle size of the electron transport material is 1~25μm; And / or, the metal oxide includes at least one of ZnO, TiO2, SnO, ZrO2, In2O3, ZnMgO, and AlZnO.

7. A method for fabricating a display device, characterized in that, Includes the following steps: A hole-functional layer and a light-emitting layer are sequentially stacked on a substrate containing an anode; After depositing the electron transport material prepared by any of the methods described in claims 1 to 4 or the electron transport material described in any of claims 5 to 6 on the surface of the light-emitting layer away from the hole functional layer, vacuum annealing is performed to remove the surface-bonded end-capping agent to obtain a metal oxide electron transport layer. A cathode is fabricated on the surface of the electron transport layer to obtain a display device; or, After depositing the electron transport material prepared by any of the methods described in claims 1 to 4 or the electron transport material described in any of claims 5 to 6 on the cathode surface of the substrate, vacuum annealing is performed to remove the surface-bonded end-capping agent to obtain a metal oxide electron transport layer. A light-emitting layer, a hole-functional layer, and an anode are sequentially stacked on the surface of the electron transport layer to obtain a display device; The vacuum annealing process includes annealing for 0.5 to 2 hours at a temperature of 70°C to 90°C and a vacuum degree not exceeding 0.0001 Pa.

8. A display device, characterized in that, The display device is prepared by the preparation method as described in claim 7.

Citation Information

Patent Citations

  • Electron transport layer and preparation method thereof, and perovskite solar cell and preparation method thereof

    CN112054123A

  • Composite material, preparation method thereof and quantum dot light-emitting diode

    CN112279949A